AN OBSERVATIONAL STUDY OF MEDICATION ERRORS AMONG PSYCHIATRIC PATIENTS IN A TERTIARY CARE HOSPITAL - Jose, Reenu; K, Krishnaveni; Maria, Jesna; Sundaram R, Shanmuga; R, Sambathkumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to evaluate the common medication error (ME), and its causes, category, and severity by using suitable questionnaire. Methods: A prospective observational study was carried out for 6 months in a psychiatric department. Demographic data, clinical history, and complete prescription were noted. Results: A total of 120 psychiatric cases were collected, among that 116 MEs were identified in which male patients were 64 (55%) and females 52 (44.8%). The number of MEs occurred due to physician was 67 (57.7%), due to nurses was 15 (12.9%), and combined was 38 (32.7%). Incomplete prescription was the main type of error that we found. About 43.1% of the error we identified was informed to the staff and and no specific action was needed for 37.1% of errors. In our study, we found that majority of 54 (46.5%) errors were categorized under category B, but there was no harm to the patient. Conclusion: The present study concluded that most of the patients admitted in the psychiatry department would experience MEs. Clinical pharmacist can play a major role in the early detection and prevention of MEs and thus can improve the quality of care to the patients.